Visualization of automated plate cutting operation using DXF file - Abd. Rahim, Norazura (2008)
This project is going to visualize the automated plate cutting application using plasma cutter. The problem behind this project is taken from problem aroused at Kinn Engineering Works, Malacca. But it will not act as the study case, this project is more to education based. The problems here are how to automate those application and what are the processes needed in order to automate it. The objective of this project is to automate the plate cutting operation and to develop a framework on how the automation could be performed. Due to cost constraint, the scope of this project was narrow down to just visualize it instead of perform it in real time application. All the drawing used is in 2 dimension drawing format. The product design for this project is in the .dwg format (Solidworks) and it will use the dxf file format as the interchange format file. This project has two main modules which are dxf reader and the animation of plate cutting process. This project is performed using project-based methodology. The drawing read by the dxf reader will be compared to the real drawing for validation purpose, and the animation process will be justified by the precision of the cutting route path. This system was developed in the C# and .NET framework environment. There are two results expected which are the system and the framework for the automated plate cutting application.